Optimal algorithm for parameter identification of nonlinear systems - Gumen, Mykola; Gumen, Tamara (Видавництво Львівської політехніки, 2010)
An optimal algorithm for parametric identification of nonlinear systems based on procedures for smoothing the experimental data and evaluation of vector parameters of the object. Parametric identification is determined by the precision of experimental data and performance evaluation procedure.
Keywords: parameter identification; smoothing the experimental data